2016
DOI: 10.1080/11250003.2016.1236843
|View full text |Cite
|
Sign up to set email alerts
|

“Opisthobranch” (mollusks) inventory of the Faro Lake: a Sicilian biodiversity hot spot

Abstract: A census of the "opisthobranch" fauna in the Faro Lake and connected canals (NE Sicily) has been realized by photo documentation and specimen samplings, carried out monthly from February 2010 to the present. A total of 47 species have been reported, nine of which are cited in the historic and recent literature (from 1969 to 2016) vs. 38 first records; six were non-indigenous species. A major number of species, 16, was found exclusively in the lake with respect to the four species localized in the canals, whils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…It consists of two connected basins, Ganzirri and Faro, each of them communicating with the sea, by ‘Faro canal’ and ‘Due Torri canal’, respectively. The lagoon complex waters are continuously renewed by marine inflows through the canals that are characterized by strong tidal currents, contrasting with the low hydrodynamics of both lakes . In Figure , the map of the area with the sampling point is provided.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of two connected basins, Ganzirri and Faro, each of them communicating with the sea, by ‘Faro canal’ and ‘Due Torri canal’, respectively. The lagoon complex waters are continuously renewed by marine inflows through the canals that are characterized by strong tidal currents, contrasting with the low hydrodynamics of both lakes . In Figure , the map of the area with the sampling point is provided.…”
Section: Methodsmentioning
confidence: 99%
“…Present knowledge, nevertheless, suffers the lack of extensive studies, so that only some major taxa and habitats, as the "Opisthobranch fauna" from brackish areas, have been exhaustively investigated (Vitale et al, 2016). Hard bottom mollusc biodiversity, in the Sicilian MS side has been explored on the local scale in the upper Infralittoral of Messina, (Cosentino & Giacobbe, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ercolania viridis published distribution was restricted to the western part of the basin (e.g. Trinchese 1872;Schmekel & Portmann 1982;Cervera et al 2004;Ballesteros et al 2016) until Vitale et al (2016) reported its presence from the central Mediterranean, based on samples from Faro Lake (Strait of Messina). Despite the fact that our sighting constitutes the easternmost Mediterranean record of this taxon, it is noteworthy to highlight that E. viridis has also been recorded from the Black Sea, where it is considered a non-indigenous species introduced through shipping from the Caribbean (Son 2010), and that its unpublished presence was noticed herein from Tunisia and Croatia (Rudman 2003;Ballesteros et al 2012Ballesteros et al -2018.…”
Section: Family Eubranchidae Odhner 1934mentioning
confidence: 99%
“…Regarding Italian waters, biodiversity assessments were recently carried out in different geographic areas (e.g. Trainito & Doneddu 2015;Furfaro & Mariottini 2016;Vitale et al 2016;Zenetos et al 2016), although the absence of specialists in the Salento Peninsula led to the fact that this taxonomic group has been poorly studied in the past, with the main articles published so far dating back to around 30 years ago (e.g. Perrone 1983Perrone , 1986.…”
Section: Introductionmentioning
confidence: 99%